Losers can win: Thermoregulatory advantages of regenerated claws of fiddler crab males for establishment in warmer microhabitats - De Grande, Fernando Rafael [UNESP]; Fogo, Bruno Rafael [UNESP]; Costa, Tânia Marcia [UNESP] (Elsevier, 2021)
Fiddler crab males present a hypertrophied claw, which is used for sexual and aggressive displays, fights with competitors, and has been proposed as an important thermoregulatory organ for heat control. Two claw morphologies can be observed within fiddler crab populations: brachychelous claws (unregenerated) and leptochelous claws (regenerated). The leptochelous morphotype presents less muscle mass and longer fingers, resulting in a less advantageous weapon in fights. Considering their slender shape, we hypothesized that the leptochelous morphotype would present lower thermal inertia and be more efficient at body heat dissipation. We evaluated the role of the fiddler crabs' claw shape as a heat sink and how this influences their distribution between unshaded and shaded microhabitats. We tested in the field whether the proportion of adult male Leptuca uruguayensis with leptochelous claws was higher in unshaded microhabitats than shaded ones. In the laboratory, we tested if heat transfer between the body and claw is higher in leptochelous males than in brachychelous males. Spontaneous waving behaviour and active time above the surface were compared between both morphotypes in the field during the hottest period of the day. Leptuca uruguayensis with regenerated claws comprised more than 60% of the sampled male population of unshaded microhabitats compared to 18% in shaded microhabitats. Leptochelous males showed a mean heat transfer between body to claw 35% higher than that observed for brachychelous males. During the hottest period of the day, brachychelous males waved approximately 28% more than leptochelous males. Moreover, brachychelous males spent less time under the sediment surface since the surface temperature increased, while activity of leptochelous males was not associated with a temperature increase. Therefore, regenerated claws may be advantageous for the establishment of L. uruguayensis males in warmer and unshaded microhabitats because they are more efficient for heat loss and allow crabs to cool down, spending less time waving. Our study shows the relevant context of winners and losers in the face of climate change and highlights the importance of morphological variations in thermoregulatory structures for the occupation of thermal niches.
Keywords: Claw shape; Climate change; Differential distribution; Thermal niches; Thermoregulatory organs